Life cycle cost analysis for the repair of a ferry terminal jetty structure - Sabtu@Othman, Hilyati (2009)
Chloride attack is one of the main causes of corrosion of steel structures exposed to marine environments. As the structure deteriorates with time, appropriate repair techniques should be applied to prevent the structure from further deterioration. Cathodic protection is one of the well-established techniques for preventing corrosion steelwork in acidic and chloride contaminated conditions. This study investigates the cost-effectiveness of repair methods for corrosion damage which could be justified by using life cycle cost analysis (LCCA). This study demonstrates the uses of LCCA in evaluating optimum maintenance decisions related to chloride-induced corrosion problems on a jetty structure. The results of the LCCA on the selected site could be used for assisting optimum decisions in arriving at cost-effective solution for the repair of corrosion-damaged structure. In a case study of a jetty structure, the analysis based on the total life cycle cost has recommended on a new deck replacement solution over the repair of existing deck